2021
DOI: 10.1177/02698811211019279
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1B receptor agonist attenuates cocaine self-administration after protracted abstinence and relapse in rats

Abstract: Background: The 5-HT1B receptor (5-HT1BR) agonist, CP94253, enhances cocaine intake during maintenance of self-administration (SA) but attenuates intake after 21 days of forced abstinence in male rats. Aims: We examined whether CP94253 attenuates cocaine intake in female rats after a period of abstinence, and if these attenuating effects persist or revert to enhancing cocaine intake during resumption (i.e. relapse) of daily cocaine SA. Methods: Male and female rats trained to lever press on a fixed ratio 5 sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…cocaine under an FR5 schedule are enhanced in male rats during maintenance of cocaine SA but attenuated after prolonged forced abstinence (Pentkowski et al, 2014 ). Recently, we replicated the latter effect in both male and female rats and showed that the effect persists even when rats are tested after resuming sessions of daily access following abstinence (Scott et al, 2021 ). These same rats also showed a decrease in cocaine cue-reactivity in response to CP94253 when tested after either 21 or 60 days of abstinence (Scott et al, 2021 ).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…cocaine under an FR5 schedule are enhanced in male rats during maintenance of cocaine SA but attenuated after prolonged forced abstinence (Pentkowski et al, 2014 ). Recently, we replicated the latter effect in both male and female rats and showed that the effect persists even when rats are tested after resuming sessions of daily access following abstinence (Scott et al, 2021 ). These same rats also showed a decrease in cocaine cue-reactivity in response to CP94253 when tested after either 21 or 60 days of abstinence (Scott et al, 2021 ).…”
Section: Discussionmentioning
confidence: 58%
“…Recently, we replicated the latter effect in both male and female rats and showed that the effect persists even when rats are tested after resuming sessions of daily access following abstinence (Scott et al, 2021). These same rats also showed a decrease in cocaine cue-reactivity in response to CP94253 when tested after either 21 or 60 days of abstinence (Scott et al, 2021). Collectively, the findings suggest that the functional effects of 5-HT 1B R agonists on cocaine reinforcement/motivation flip from facilitatory during maintenance of daily SA to inhibitory after prolonged abstinence in both males and females.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations